Microwave Dielectric Properties of (1-x) Li2MoO4–xMg2SiO4 Composite Ceramics Fabricated by Cold Sintering Process - Ji, Yuping; Song, Kaixin; Luo, Xinjiang; Liu, Bing; Barzegar Bafrooei, Hadi; Wang, Dawei (Frontiers in Materials, 2019)
Cold sintering process was successfully employed to fabricate (1-x) Li2MoO4–xMg2SiO4 (LMO-xMSO) microwave dielectric ceramics for 5G enabled technology. Dense LMO-xMSO ceramics were obtained with a high relative density in the range of 85–100% under the conditions of 200°C and 500 MPa in an hour. X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), and Raman spectroscopy showed that both the LMO and MSO phases co-exist in all composite ceramics, and that there is no detectable secondary phase. Composites of LMO-xMSO (0 < x < 0.3) resonated at microwave frequency (~9 GHz) with a low relative permittivity (εr) of 5.05~5.3, and a high microwave quality factor (Q × f) of 9,450~24,320 GHz, which are attractive for the applications of 5G enabled components.